2014
DOI: 10.7554/elife.01267
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor NRSF contributes to epileptogenesis by selective repression of a subset of target genes

Abstract: The mechanisms generating epileptic neuronal networks following insults such as severe seizures are unknown. We have previously shown that interfering with the function of the neuron-restrictive silencer factor (NRSF/REST), an important transcription factor that influences neuronal phenotype, attenuated development of this disorder. In this study, we found that epilepsy-provoking seizures increased the low NRSF levels in mature hippocampus several fold yet surprisingly, provoked repression of only a subset (∼1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 106 publications
5
139
0
2
Order By: Relevance
“…In this context, REST plays a central role in the determination of the neuronal fate (46), as well as in the modulation of neuronal activity and plasticity (9). The role of REST in the onset of pathologies is complex, acting under some circumstances as an oncogene and under other conditions as a promoter of insult-induced neuronal death (brain ischemia, HD) (11,13,41) or dysfunction (epilepsy) (42). Thus, a fundamental objective of next investigations would be to express the REST-modulating probes in vivo in experimental models of brain pathologies associated with REST overexpression or hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, REST plays a central role in the determination of the neuronal fate (46), as well as in the modulation of neuronal activity and plasticity (9). The role of REST in the onset of pathologies is complex, acting under some circumstances as an oncogene and under other conditions as a promoter of insult-induced neuronal death (brain ischemia, HD) (11,13,41) or dysfunction (epilepsy) (42). Thus, a fundamental objective of next investigations would be to express the REST-modulating probes in vivo in experimental models of brain pathologies associated with REST overexpression or hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its crucial role in several neuropathologies (10,11,13,14,41,42), various molecular strategies have been developed to target REST activity, including decoy oligodeoxynucleotides, interfering peptides, and stable expression of dominant-negative/constitutively active forms of REST (14,16,17). These approaches have been applied to a number of pathological models, including HD and medulloblastoma, encountering various levels of success.…”
Section: Discussionmentioning
confidence: 99%
“…For example, inducible cAMP early repressor (ICER) has been suggested to play a role in epileptogenesis as it suppresses kindling (Kojima et al 2008;Porter et al 2008). Other candidates include cAMP response element (CREB), controlling differential expression of genes in human epileptic cortex (Beaumont et al 2012), and repressor element-1 silencing transcription factor (NRSF) shown to repress epileptogenesis in a kindling model and reported to regulate target genes relevant for neuronal network remodeling in kainate-induced SE (Hu et al 2011;McClelland et al 2014).…”
Section: Molecular Mechanisms Of Epileptogenesismentioning
confidence: 99%
“…In the latter case several reports have pointed to its involvement in the shift from physiological to pathological conditions. An upregulation of REST in ischemic seizures has been interpreted as a potentially adverse effect, leading to neurodegenerative processes [8,9], even if the relationship between REST levels and silencing of neuronal genes has been reported to be quite complex and specific [10]; on the other hand, the same up-regulation following network hyperexcitation has been…”
Section: Introductionmentioning
confidence: 99%